亚院二年级学生使用方位词“里”与“中”的偏误分析 MISTAKES OF USING DIRECTIONAL NOUN “LI” AND “ZHONG” IN STBA-PIA STUDENTS SEMESTER IV T.A. 2018/2019 - Dewi Kartika (Journal of Language, Literature and Teaching, 2021)
This study aims to describe the types of errors and the factors that cause errors in the use of directional nouns "li" and "zhong" made by STBA-PIA students in the fourth semester of T.A. 2018/2019. The research method used is descriptive qualitative, namely to describe the types of errors and the factors that cause errors. The instruments used in this research are elicitation techniques and interview techniques. The research subject was taken using snowball sampling technique, which was as many as 25 subjects. The results of the research conducted by researchers on STBA-PIA students in semester IV T.A 2018/2019 are 10 omission errors, 6 addition errors, 14 mis formations and 3 disordering. Meanwhile, the factors that cause errors are of two types, namely interlingual errors, which are 7 respondents and intralingual errors, which are 15 respondents.Keywords: Language Errors, Directional Nouns “Li” and “Zhong”.